2009
DOI: 10.1007/s11606-009-0936-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Osteoporosis Screening and Recommendations for Osteoporosis Screening in Older Adults

Abstract: BACKGROUND: Osteoporosis screening rates are low, and it is unclear which patient factors are associated with screening and physician recommendations for screening. OBJECTIVE:To identify patient characteristics associated with osteoporosis screening recommendations and receipt of screening in older adults. DESIGN:Cross-sectional mailed survey. PARTICIPANTS:Women and men ≥60 years old living in or near western Pennsylvania.MEASUREMENTS: Sociodemographic characteristics and osteoporosis-related data, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The publications describe in detail the importance of these risk factors in the development of the disease. These results fully coincide with other authors who have applied this kind of analysis in their studies [7,9,32], although they differ partially from those obtained by other authors in Spain [33], who used the heel quantitative ultrasound technique as an bone mineral density (BMD) reading. Some investigators [34,35] also mention smoking and alcohol as important factors associated with a higher incidence of this disease, although we were unable to confirm this point.…”
Section: Main Risk Factors For Osteoporosissupporting
confidence: 86%
See 1 more Smart Citation
“…The publications describe in detail the importance of these risk factors in the development of the disease. These results fully coincide with other authors who have applied this kind of analysis in their studies [7,9,32], although they differ partially from those obtained by other authors in Spain [33], who used the heel quantitative ultrasound technique as an bone mineral density (BMD) reading. Some investigators [34,35] also mention smoking and alcohol as important factors associated with a higher incidence of this disease, although we were unable to confirm this point.…”
Section: Main Risk Factors For Osteoporosissupporting
confidence: 86%
“…The study of osteoporotic fractures, a large, prospective US study, identified 14 clinical risk factors for osteoporotic hip fracture in multivariable models: age, maternal hip fracture, personal history of any fracture from the age of 50, height, poor self-rated health, no weight gain, hyperthyroidism, not walking for exercise, lack of ambulation, inability to rise from a chair, poor vision, high resting pulse, and current use of benzodiazepines, anticonvulsants, or caffeine [9].…”
Section: Introductionmentioning
confidence: 99%
“…The mean rate of screening in one primary care group practice was 56% [12]. Less than 50% of 1200 adults aged 60 years or older surveyed in the north-eastern USA said that their doctor recommended osteoporosis screening [13].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of outpatient visits that addressed osteoporosis is a testimony of increasing need and demand for osteoporosis care in older patient population. Growing numbers of older people with multiple co-morbidities in the USA 26 continue to increase demand on PCPs for continuity of care for chronic diseases 14,27 . Osteoporosis, a chronic disease of old age demands similar care with continuation and hence the role of PCPs is important in managing this bone disease.…”
Section: Discussionmentioning
confidence: 99%